ปัจจัยกำหนดความสามารถในการทำกำไรของธนาคารพาณิชย์ในประเทศไทย - เที่ยงตรง วิไลวรรณ; วิศวโกศล เกตุแก้ว; จันทร์จรัส นงค์นิตย์ (Phranakhon Rajabhat Research Journal : Humanities and Social Sciences, 2017)
This study aims to examine the factors influencing the profitability of the 11 Thai commercial banks listed on the Stock Exchange of Thailand. The dependent variable is profitability of commercial banks measured by 3 measurements while independent variables including capital ratio, size of bank, total loans and leases, total deposits, share deposits, interest expense, investment in securities, SET Index, and Gross Domestic Product (GDP). The data are collected from DATA STREAM during the period 2005-2015. Three multiple regression models according to the measurement of commercial bank profitability are employed including 1) Rate of return (ROA), 2) Return on common shareholders’ equity, and 3) Earning per share (EPS). The empirical results found that factors influencing each model of bank profitability were vastly difference. The factors influencing the profitability of the Thai commercial banks depended on each profitability measurements. Furthermore, the results implied that the factors that related to commercial banks profitability are interest expenses, the total loans and leases, capital ratio, GDP and the bank size. These findings could be useful for making decision and considering factors influencing the commercial bank profitability.